Managerial Behavior and the Social Responsibility Debate: Goals Versus Constraints - Keim, Gerald D. (Academy of Management Journal, 1978)
This paper examines the “popular” view of the social responsibility of business as advanced by George Steiner, Keith Davis and others and the “traditional” position so frequently associated with ec...